2009
DOI: 10.1111/j.1365-2567.2009.03079.x
|View full text |Cite
|
Sign up to set email alerts
|

Bone morphogenetic protein‐6 induces the expression of inducible nitric oxide synthase in macrophages

Abstract: SummaryBone morphogenetic proteins (BMPs) are members of the transforming growth factor-b (TGF-b) superfamily. In the present study, we investigated the effect of BMPs on the production of inducible nitric oxide synthase (iNOS) in the murine macrophage cell line, RAW 264.7, and in mouse peritoneal macrophages. Among the BMPs, only BMP-6 induced iNOS expression in a time-dependent and dose-dependent manner in both cell types. Induction of iNOS was inhibited by both cycloheximide and actinomycin D, indicating th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 27 publications
(49 reference statements)
0
24
0
Order By: Relevance
“…However, whether Bmp/Smad signaling is altered in Hjv −/− macrophages and/or whether crosstalk exists between the inflammatory response and Bmp/Smad signaling is not currently known. Bmp6 can induce NO production in macrophages independent of Smad [ 42 ], and inflammatory stimuli can reduce Smad1/5/8 phosphorylation in macrophages [ 43 ]. However, we found similar levels of phosphorylated Smad1/5/8 levels between Hjv −/− and wild-type macrophages following stimulation with heat-killed E. coli ( Supplementary Figure S6A ).…”
Section: Resultsmentioning
confidence: 99%
“…However, whether Bmp/Smad signaling is altered in Hjv −/− macrophages and/or whether crosstalk exists between the inflammatory response and Bmp/Smad signaling is not currently known. Bmp6 can induce NO production in macrophages independent of Smad [ 42 ], and inflammatory stimuli can reduce Smad1/5/8 phosphorylation in macrophages [ 43 ]. However, we found similar levels of phosphorylated Smad1/5/8 levels between Hjv −/− and wild-type macrophages following stimulation with heat-killed E. coli ( Supplementary Figure S6A ).…”
Section: Resultsmentioning
confidence: 99%
“…While several different factors have been shown to regulate macrophage and microglia activation, the effect of BMPs is still not completely characterized [39, 40, 76, 77]. BMP6 regulates expression of inflammatory markers such as IL-6, IL-1β, and nitric oxide synthase in macrophages [7880]. In addition, more recent studies indicate that BMP exposure particularly leads to the M2 or anti-inflammatory phenotype of the macrophages promoting tissue repair [8184].…”
Section: Discussionmentioning
confidence: 99%
“…This protumorigenic effect of BMP-6 only in vivo implicates a paracrine mechanism. Along this line, it has recently been reported that BMPs regulate immune effector cells including macrophages (9,10). To investigate whether macrophages mediate the protumorigenic effect of BMP-6 in RCC, clodronate liposome was used to selectively remove macrophages (30).…”
Section: Bmp-6 Is Protumorigenic In Rcc Cellsmentioning
confidence: 99%
“…Although originally reported as factors that induce bone and cartilage formation (3), BMPs have been shown to be critical for development (4)(5)(6). More recently, we and others have reported that BMPs regulate the immune system as BMP-6 inhibits B-and T-cell proliferation (7,8) and activates macrophages (9,10). In the context of RCC, BMP-4, -6, and -7 are often overexpressed (11,12), whereas BMP antagonist Sclerostin domain-containing-1 (SOSTDC1) is downregulated (13).…”
Section: Introductionmentioning
confidence: 99%